Value Distribution and Arbitrary-Order Derivatives of Meromorphic Solutions of Complex Linear Differential Equations in the Unit Disc - Hai-Ying Chen (Mathematics, 2019)
In this paper, we investigate the value distribution of meromorphic solutions and their arbitrary-order derivatives of the complex linear differential equation <semantics> f ′ ′ + A ( z ) f ′ + B ( z ) f = F ( z ) </semantics> in <semantics> Δ </semantics> with analytic or meromorphic coefficients of finite iterated p-order, and obtain some results on the estimates of the iterated exponent of convergence of meromorphic solutions and their arbitrary-order derivatives taking small function values.